PENGARUH METODE STRUKTURAL ANALITIK SINTETIK (SAS) TERHADAP PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN - Karniawati, Karniawati; Hamdani, Agus; Damayanti, Deasy Aditya; Naida, Winka (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study entitled "The Influence of Synthetic Structural Analytical Methods (SAS) on Improving Beginning Reading Ability." Covid-19. Yesterday's pandemic conditions left a number of interesting things in education, such as learning that is done online and is less effective. This is because those who have just learned to read at the beginning will have difficulty increasing their abilities. Online learning conditions do not allow teachers and students to meet face to face, while in learning to read the beginning it must be carried out directly. There are several indicators that cause reading difficulties in students, some of which are as follows. 1) students do not know the letters 2) students do not know the meaning of the sentences read. Therefore, researchers tested the use of the SAS method as a method of learning to read beginning. The research was conducted using a quantitative approach to the experimental method in improving the reading ability of grade 1 students at SDN 2 Ciudian Singajaya. The design in this study was a one-group pretest-posttest pre-experimental. The research population was class I students at SDN 2 Ciudian Singajaya with a total of 17 people using the quota (population) sampling technique. The data collection techniques are in the form of tests and observations. Testing the difference in values ​​is only carried out on the average of the two values, and for this purpose a technique called the z-test is used. The results obtained were: (1) the average ability obtained by students before being treated with the SAS method (pretest) was 81.37 (Enough); (2) the ability of the average score of students after being treated with the SAS method (post-test) is 91.17 (Very Good); (3) this study resulted in an acceptable H1, namely the use of the SAS method was effective in improving the reading ability of class I students at SDN 2 Ciudian Singajaya.